Conceptualization and Positioning of the Two Malleolus Bones in the Qur'an: A Medical Data Approach - Amirhamzeh Salarzai (پژوهش‌های فقهی مسائل مستحدثه, 2023)
Received: 2023 May 23  |   Recieved in revised form: 2023 Jul 7   |   Accepted: 2023 Aug 6   |   Published: 2023 Oct 23Interdisciplinary research plays a crucial role in the advancement and revitalization of scientific knowledge. By combining expertise from various related fields, it promotes scientific progress and resolves uncertainties, thus clarifying complex concepts. Analyzing and revising jurisprudential opinions to align them with Muslim medical data is essential for the dynamic nature of Islamic interpretation (ijtihād). The article focuses on the method of cleaning (Tahārah) the feet during ablution (Vuzū), specifically examining the anatomy of the Malleolus bones in relation to the term "Ka’bīn" mentioned in the sixth verse of Surah Mā'idah. The prevailing opinion among renowned jurists, as quoted by Allameh Helli, regarding the method of cleaning the feet is subject to scrutiny. The author, based on the concept and positioning of the Ka'b on the human foot, calls for a substantial revision of the related jurisprudential decrees (fatwā) on anointing (maṣḥ) and its procedure. Accordingly, the sufficiency of cleaning the feet, even with a single finger, which is the widely accepted view among Shiite jurists according to Helli, becomes a debatable aspect for ensuring foot purity. Furthermore, medical terminology and anatomical evidence demonstrate that Ka'bīn encompasses both the external and internal sides of the foot. Additionally, data derived from medical osteology of the ankle challenges a significant portion of the jurisprudential fatwā pertaining to the principle of cleaning the feet and its method.Salarzai, A. (2023) Conceptualization and Positioning of the Two Malleolus Bones in the Qur'an: A Medical Data Approach. Quarterly of New Perspectives in Islamic Jurisprudence, 1 (1) 28-57. Doi: https://doi.org/10.22091/RCJL.2023.8739.1009.